EVALUATION OF MOSQUITOCIDAL POTENTIAL OF DRYPETES ROXBURGHII (WALL.)GREEN MATURE FRUITS AGAINST IMMATURES OF CULEX QUINQUEFASCIATUS SAY AND ANOPHELES STEPHENSI LISTON - KOYEL MALLICK HALDAR,; GOUTAM CHANDRA, (International Journal of Pharma and Bio Sciences, 2015)
Mosquito larvicidal potential of mature fruits of Drypetes roxburghii was investigated against mosquito Culex quinquefasciatus Say and Anopheles stephensi Liston. In the larvicidal bioassay with crude extract against all four instars 3rd instar larvae of both species was noticed to be more susceptible to death in terms of LC50 and LC90 values. Among the solvent extracts of fruits prepared using six solvents [viz. petroleum ether, benzene, ethyl acetate, chloroform: methanol (1:1 v/v), acetone and absolute alcohol] ethyl acetate extract was most potent solvent extract against 3rd instar of both mosquito species with LC50 and LC90 values 77.03ppm, 205.64 ppm for Cx. quinquefasciatus and 49.535ppm, 108.88ppm for An. stephensi respectively. Qualitative analysis traced the presence of some phytochemicals. Upon test on non-target organisms like Diplonychus annulatum, Poecilia reticulata, larvae of Toxorhynchites splendens both crude and ethyl acetate extract proved relatively nontoxic.